Islam in the Practice of Maritime Economy in Indonesia - Sodiman; Dudung Abdurahman; Ahmad Muttaqin (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The maritime economy is formed as a result of the vast ocean area's geographical situation, the archipelago's rich natural resources, and the establishment of international trade routes as a result of the archipelago's strategic location at the intersection of two oceans and continents, namely the Indian Ocean and the Pacific Ocean, and the Asian continent and the Australian continent. In Indonesia, Islamic values impact marine economic practices; how do Islamic values form the spirit of the maritime economy? How do Islamic principles influence the archipelago's marine economy? How did your talents as an accomplished sailor change after Indonesia gained independence? Studies to answer these scientific questions are important for at least two reasons: first, to explain why Islam has had such a profound influence on the formation of the maritime economic ethos in Indonesia; and second, to explain why Islam has had such a profound influence on the formation of the maritime economic ethos in Indonesia. Third, Islam is the largest community in the archipelago. This paper is a critical library research paper, and the following data collection strategies were used for this study: (1) arranging the appropriate equipment, (2) constructing a working bibliography, (3) organizing time, and reading and taking research notes. Analyze data using content analysis. Content analysis is a technique for analyzing and comprehending literature. To begin with, the primary source of Islam, the Quran, contains a wealth of information regarding maritime trade. Second, the effect of Islam on maritime economic practices in Indonesia is both a cause and a result of Islam's spread via maritime trade channels. Third, the development of the marine economy in modern Indonesia may be seen in the maritime spirit, which is still a living value and a belief among maritime economic actors and coastal populations that rely on maritime resources for their income.